Sudden Death of a Pregnant Woman in Third Trimester with No Risk Factor - Asli Goker; Melek Civi; Ozgur Bayturan; N. Kemal Kuscu (Case Reports in Obstetrics and Gynecology)
Acute myocardial infarction in pregnancy is rare and life-threatening for both the mother and the fetus. We present the case of a 31-year-old previously healthy woman with no risk factors at 32 weeks of gestation who applied with vomiting, dyspnea and orthopnea. A respiratory arrest developed followed by loss of the fetal viability, cardiac arrest, and failure of resuscitation. We aim to raise awareness about the clinical approach to pregnant patients who are to be considered with a broad spectrum of differential diagnosis.